Skill Level of the Backhand Overhead Lob Shot at the Handil III Badminton Association, Gambut District, Banjar Regency - Mushlih, Muhammad; Erliana, Mita; Hamid, Abdul (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
This research aims to determine the proficiency level in the Backhand Overhead Lob shot at PB. Handil III, Gambut District, Banjar Regency. This research is quantitative. The method used by researchers in this research is a survey method with test and measurement techniques carried out by (Poole James, 2011). The tests and measurements were conducted on PB's Proficiency Level of Backhand Overhead Lob Shots. Handil III, Gambut District, Banjar Regency. The population in this study were all PB. Handel III, Gambut District, Banjar Regency, totalling 15 people. The sampling technique uses total sampling. So, the sample size is 15 people. The research results showed that the skill of Backhand Overhead Lob hitting PB. Handil III Gambut District with the "Very Good" category, namely 0 or (0%), then for the "Good" category, there were seven students or (47%), then in the "Fair" category, there were three students or (20%), then in the "Poor" category there were four students or (27%) and finally in the "Very Poor" category, there were one student or (7%). Next, for an average of 24, the skill of the Backhand Overhead Lob shot is PB. Handil III, Gambut District is in the "Good" category.